Prevalence of respiratory distress syndrome in premature twins compared to premature singletons - Emina Hadžimuratović; Amina Selimović; Admir Hadžimuratović; Verica Mišanović; Velma Rebić; Lejla Kurtalić (Medicinski glasnik, 2024)
Aim: To estimate prevalence of respiratory distress syndrome in preterm twins compared to preterm singletons. Methods: This is a retrospective observational point prevalence study conducted at the level of three neonatal intensive care units. Medical records of all preterm newborns (<37 weeks of gestation) with respiratory distress syndrome treated in a two-year period were reviewed. The birth order of twins, gestational age and mortality were analyzed. Results: Out of 809 preterm newborns, 104 (12.9%) were twins. Median gestational age at birth was 30.3 (IQR 31.4-34.2) weeks. Respiratory distress syndrome was diagnosed in 525 (64.9 %) preterm newborns, of which 441 singletons and 84 twins. Prevalence of respiratory distress syndrome in first-born twins was not significantly higher compared with singletons, 67.3% (35/52) vs. 62.6 % (441/705), respectively (p=0.06). Prevalence of respiratory distress syndrome in second-born twins was 94.2 % (49/52), which was significantly higher compared with both singletons and first-born twins (p<0.001). The mortality rate of preterm newborns was significantly higher in second-born twins compared with singletons and first-born twins, 15.4 % vs. 6.8 % (p<0.001) and 15.4 % vs. 5.5% (p<0.001), respectively. Conclusion: There was a higher risk of respiratory distress syndrome and higher mortality rate in twins compared with singletons, but only in second-born twins the difference was statistically significant.
Keywords: preterm birth; res-piratory distress syndrome; twin pregnancy